2010
DOI: 10.1029/2009ja014498
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a possible neutron burst associated with a lightning discharge?

Abstract: [1] During routine measurements of the background count rate of low-energy neutrons with a standard He-3 detector tube in the city of Sao Jose dos Campos, Brazil, we observed a sudden and sharp increase in the neutron count rate. This sharp increase was practically simultaneous with a lightning discharge that occurred in the vicinity of the tube detector. Since sources of spurious signals, such as malfunctioning equipment and electrical transients, have been eliminated as causes of the observed event, we are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…Chilingarian et al (2010) report a neutron excess during a bright gamma-ray glow of 2009 September 19, with duration ∼10 minutes. While the neutron events seen by Kuzhevskii (2004) and Martin and Alves (2010) were more than an order of magnitude higher than the background levels in their instruments, the neutron event reported by Chilingarian et al (2010), shown in their Fig. 3, is only a 3 % excess over background.…”
Section: Observations Of Neutrons From Thunderstormsmentioning
confidence: 71%
See 2 more Smart Citations
“…Chilingarian et al (2010) report a neutron excess during a bright gamma-ray glow of 2009 September 19, with duration ∼10 minutes. While the neutron events seen by Kuzhevskii (2004) and Martin and Alves (2010) were more than an order of magnitude higher than the background levels in their instruments, the neutron event reported by Chilingarian et al (2010), shown in their Fig. 3, is only a 3 % excess over background.…”
Section: Observations Of Neutrons From Thunderstormsmentioning
confidence: 71%
“…More recent ground-based observations were made by Kuzhevskii (2004), Chilingarian et al (2010), and Martin and Alves (2010). Kuzhevskii (2004) observed several events from a station in Moscow.…”
Section: Observations Of Neutrons From Thunderstormsmentioning
confidence: 93%
See 1 more Smart Citation
“…[26] reports short and sharp increases in low energy n count rate simultaneous with a lightning discharge occurring in vicinity of the detector. Measurements with high time resolution at Tian Shan indicate highly correlated short n signals (bursts ≈ 200 − 400µs) observed by three types of detectors placed at different positions: He3 counters (with and without polyethylene moderator) and neutron monitor (NM) in time coincidence…”
Section: Ground Based Cr / Other Particle Observations Related To Atmmentioning
confidence: 99%
“…So with this chart, normal background noise radiation could be verified or if there had been in this time a different variation indicating presence of another generating source as lightning, rain and thick clouds crossing the region. To determine periodicities in long series of intensity measurements, Fast Fourier Transform (FFT) analysis was made (power spectra) thus observing periods related to various environmental phenomena in the region [7][8][9][10].…”
mentioning
confidence: 99%